Employee adaptive performance and job satisfaction during organizational crisis: the role of self-leadership (2019)
This study tests the hypothesis that self-leadership is positively related with employee adaptive performance and job satisfaction in rapid change and unpredictable work environments. This assump- tion was tested through a quasi-experimental study regarding the implementation of a self-leadership training programme in the Private Banking department of an international bank. Change in private bankers’ self-leadership, adaptive performance and job satisfaction was measured three times, over a period of 8 months. During the fourth month of the training programme implementation, the bank underwent an unexpected bailout. Fifty-two private bankers were randomly assigned to an experi- mental group (n = 28) and to a control group (n = 24). The results showed an increase in self-leadership, adaptive performance and job satisfaction for the experimental group, while job satisfaction decreased for participants in the control group. Our findings suggest that change in the level of self-leadership is positively related with change in the level of adaptive performance and job satisfaction over time. This study presents new evidence that individual adaptive performance and job satisfaction can be enhanced through self-leadership training. Self-leadership training can be used as a valuable tool to help organizations improve employees’ adaptive performance and job satisfaction, especially during organizational crisis.